EFFORTS TO INCREASE FINE MOTORIC ABILITY THROUGH SQUEEZING WATER ACTIVITIES WITH SPONGE MEDIA PLAYING GROUPAL FURQOON PAUD OF KLATEN GRAND MOSQUE - Siti Khoiriyah Rohimah; Ihda A'yunil Khotimah (QURROTI : JURNAL PENDIDIKAN ISLAM ANAK USIA DINI, 2022)
Fine morotic is the ability to move related to smooth muscles. Early childhood development is the foundation in carrying out developmental tasks in adulthood. This study aims to determine the process of implementing the activity of squeezing water with sponge media in improving fine motor skills and to find out how much it increases fine motor skills in the PAUD Al Furqoon Playgroup of Masjid Raya Klaten after the implementation of these activities. This research method is a Classroom Action Research (CAR) with two cycles, each cycle consisting of four stages: planning, action implementation, observation, and reflection. Data collection techniques with interviews, observation, performance and documentation. The subjects of this study were the children of the PAUD Al Furqoon Playgroup of the Great Mosque of Klaten, totaling 25 children. The results of this study indicate an increase in fine motor skills through squeezing water with sponge media in children's Play Group PAUD Al Furqoon Masjid Raya Klaten. The increase in children's motor skills through squeezing water with sponge media are: from pre-cycle 20%, then in the first cycle it increases to 54%, until the second cycle the increase is 82%. Then there was an increase of 62%. So it was concluded that squeezing water with a sponge media can improve fine motor skills in children in the Al Furqoon PAUD Play Group Klaten Grand Mosque.